The Protection of Journalists in Non-International Armed Conflict based on the International Humanitarian Law: an Indonesian Case - Meta Selvia Mardiana (2013)
The title of this thesis is a study of International Humanitarian Law on the Non-International Armed Conflict. This study aimed to know about The International Humanitarian Law can be applied in solving Journalist an Indonesian case and to know about kinds of protection should be given to Journalist in Non-International Armed Conflict. The research is normative jurisdicial that is juridical principles, doctrines and the source of law in the sense of philosophical juridical international humanit